Sosialisasi Pencegahan Pernikahan Dini Melalui Literasi Perencanaan Keuangan untuk Masa Depan - Hasibuan, Kalijunjung; Laili, Uut Nur; Akmalia, Riska; Rahmawati, Sintia; Fitriani, Fitriani (Welfare : Jurnal Pengabdian Masyarakat, 2023)
The community service entitled "Socialization of Premature Marriage Prevention through Financial Planning among Students" aims to increase students' financial literacy as an effort to prevent early marriage. Mentoring methods involve workshops, training and financial literacy campaigns, with active involvement of students and collaboration with students. Results include increased financial literacy, active student participation in prevention activities, the emergence of new institutions in school policy, and positive changes in attitudes and behavior among students. The conclusion confirms that the financial literacy approach is effective in preventing early marriage, strengthening the role of students as agents of change, and supporting positive social change in the school environment.